Respuesta :
We solve the system by applying the following steps:
1) Write two of the variables in terms of the third variable. For this case we write x, y in terms of z.
2) Substitute the expressions in the first equation since it relates all the variables.
3) Clear z.
4) with the value of z, find x, y
Answer:
A. x = 0, y = 1, z = 2
See attached image.
1) Write two of the variables in terms of the third variable. For this case we write x, y in terms of z.
2) Substitute the expressions in the first equation since it relates all the variables.
3) Clear z.
4) with the value of z, find x, y
Answer:
A. x = 0, y = 1, z = 2
See attached image.
![Ver imagen carlosego](https://us-static.z-dn.net/files/d68/2c16b66d4e25486a29be263e394c21a4.jpg)
![Ver imagen carlosego](https://us-static.z-dn.net/files/d6a/2eb66367f2529aee1807068c449843f5.jpg)